Assessment of Caesarean Section Rates at Kathmandu Model Hospital Using the Robson’s Ten Group Classification System - Poudel, Rekha; Dangal, Ganesh; Karki, Aruna; Pradhan, Hema Kumari; Shrestha, Ranjana; Bhattachan, Kabin; Bajracharya, Nishma; Tiwari, Kenusha Devi; Bharti, Sonu (Journal of Nepal Health Research Council, 2020)
Background: Aims of this study was to assess the caesarean section rate and identify the indications contributing to the same using the Robson’s Ten Group Classification System at Kathmandu Model Hospital.Methods: This was a retrospective study conducted at Kathmandu Model Hospital among women who underwent caesarean section from 1 January to 31 December, 2018 and were grouped according to Ten Group Classification System. The overall caesarean section rate and the contribution of each group was calculated.Results: The overall caesarean section rate was 66.1% (494 among 747 total deliveries) in 2018. Nullipara, singleton cephalic, >= 37 weeks, spontaneous labor (Group 1) was the major (24.2%) contributor to the overall caesarean section rate followed by previous caesarean section, singleton cephalic, >=37 weeks (Group 5, 22.6%) and nullipara, singleton cephalic, >=37 weeks, induced or caesarean section before labor (Group 2, 18.8%). Also, the caesarean section rate was 49.5% in nullipara, thus increasing the trend of caesarean section for previous caesarean section in future.Conclusions: Efforts must be focused more on Group 1, 2 and 5 to decrease the increasing trend of caesarean section Promoting vaginal delivery in nullipara and facilitating vaginal birth after caesarean are the most relevant areas of intervention. Keywords: Caesarean section; Robson ten group classification system; vaginal birth after caesarean.